2021
DOI: 10.1111/1756-185x.14228
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of renal remission and relapse‐free rate in initial‐ and delayed‐onset lupus nephritis

Abstract: Introduction Lupus nephritis (LN) is a major manifestation of systemic lupus erythematosus (SLE) which contributes to significant morbidity and mortality. It is unclear whether the timing of LN onset influences renal outcome. This study aimed to investigate differences in clinical features—particularly the relapse‐free rate—in remission duration from induction therapies for LN and the onset timing of LN after the development of SLE. Methods We enrolled 66 LN patients from January 2004 to March 2020. We collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…As shown in Table 1 , the present study showed the same results with a larger population and a longer follow-up duration. In addition, previous studies have suggested factors that could predict LN relapse from clinical characteristics and laboratory findings at the time of LN diagnosis, including male sex [ 6 , 36 ], delayed-onset LN [ 38 ], presence of HTN [ 6 ], and elevated baseline creatinine [ 10 ]. In the present study, as shown in Table 1 , proportions of patients with extremely severe proteinuria (over 6 g) and hypoalbuminemia (less than 2.0 g/dL) were higher in the relapsed group than in the relapse-free group.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table 1 , the present study showed the same results with a larger population and a longer follow-up duration. In addition, previous studies have suggested factors that could predict LN relapse from clinical characteristics and laboratory findings at the time of LN diagnosis, including male sex [ 6 , 36 ], delayed-onset LN [ 38 ], presence of HTN [ 6 ], and elevated baseline creatinine [ 10 ]. In the present study, as shown in Table 1 , proportions of patients with extremely severe proteinuria (over 6 g) and hypoalbuminemia (less than 2.0 g/dL) were higher in the relapsed group than in the relapse-free group.…”
Section: Discussionmentioning
confidence: 99%
“…3 Lupus takes a chronic course with remitting and relapsing patterns. 4,5 Furthermore, repeated flares can lead to chronic damage accrual, especially for lupus nephritis patients. Hence, instituting measures to ensure prompt diagnosis of flares will protect against damage development.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%